(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study examines the power of total comprehensive income to predict the annual future net cash flow from operating activities and future total comprehensive income compared with the power of net income to predict the annual future net cash flow from operating activities and future net income, for the financial firms listed on Damascus Securities Exchange. The study population consisted of financial companies listed on the Damascus Securities Exchange, where it was to rely on the financial statements of seven banks coincided with the study sample conditions during the period (2010- 2015). The study used models developed in previous literature in order to achieve the objective of the study. The study found that there is no relationship between total comprehensive income and net income with the annual cash flow. While there is a significant correlation between both comprehensive and net income with the future profit figure, total gross income does not outweigh net income by predicting the future profit figure. تختبر هذه الدراسة مدى قوة إجمالي الدخل الشامل على التنبؤ بالتدفق النقدي الصافي السنوي المستقبلي من الأنشطة التشغيلية وإجمالي الدخل الشامل المستقبلي للشركات المالية المدرجة في سوق دمشق للأوراق المالية مقارنةً بقوة صافي الدخل على التنبؤ بالتدفق النقدي الصافي السنوي المستقبلي من الأنشطة التشغيلية وصافي الدخل المستقبلي لهذه الشركات. تكوّن مجتمع الدراسة من الشركات المالية المدرجة في سوق دمشق للأوراق المالية، حيث تمّ الاعتماد على البيانات المالية الخاصة بسبعة مصارف توافقت مع شروط عينة الدراسة خلال الفترة (2010- 2015). ولتحقيق أهداف الدراسة تم استخدام النماذج المطّورة في الأدبيات السابقة. توصلت الدراسة إلى عدم وجود علاقة ذات دلالة معنوية بين كلٍ من إجمالي الدخل الشامل وصافي الدخل مع التدفق النقدي المستقبلي السنوي من الأنشطة التشغيلية، بالتالي عدم إمكانية تفوّق أحدهما على الآخر. بينما توجد علاقة ذات دلالة معنوية بين كلٍ من إجمالي الدخل الشامل وصافي الدخل مع رقم الربح المستقبلي، إلا أن إجمالي الدخل الشامل لا يتفوق على صافي الدخل بالتنبؤ برقم الربح المستقبلي.